Sustainable investing : a path to a new horizon - Herman, Bril (Routledge, 2020)
"This book tells the story of how the convergence between corporate sustainability and sustainable investing is now becoming a major force driving systemic market changes. The idea and practice of corporate sustainability is no longer a niche movement. It is on the agenda of the boardrooms of leading corporations on all continents. At the same time, investors are increasingly paying attention to sustainability factors in their analysis and decision making thus reinforcing market transformation. In this book, high-level practitioners and academic thought leaders, including contributions from John Ruggie, Fiona Reynolds, Johan Rockström, and Paul Polman, explain the forces behind these developments and show how the application of technology and organizational innovation can renew markets from within thus delivering better outcomes for societies. The contributors highlight (a) that systemic market change is influenced by various contextual factors that impact how sustainable investing is perceived and practiced; (b) that the integration of ESG factors in investment decisions is impacting markets on a large scale and hence change practices of major market players (e.g., pension funds); and (c) that technology and the increasing datafication of sustainability act as further accelerators of such change. The book goes beyond standard economic theory approaches to sustainable investing and emphasizes that capitalism founded on more real-world (complex) economics and cooperation can strengthen ESG integration. Aimed at both investment professionals and academics, this book gives the reader access to more practitioner-relevant information and it also discusses implementation issues. The reader will gain insights into how "mainstream" financial actors relate to sustainable investing"--